Competition model and coordination mechanism considering strategic customer behavior under vendor‐managed inventory. (3rd June 2019) - Cai, Jianhu; Zhou, Qian; Sun, Jianyue; Hu, Xiaoqing; Feng, Cuiying; Li, Xuejiao
Abstract: This paper proposes the vendor‐managed inventory (VMI) decision model that considers strategic customer behavior. Decision differences between the Stackelberg game equilibria and the supply chain (SC) coordination are compared under the VMI mode. A comparison of the optimal decisions under the VMI mode and the retailer‐managed inventory (RMI) mode is made. The SC members' preferences for the two inventory modes are obtained under different wholesale price conditions. Then, the option contract is introduced to coordinate the SC, and possible allocation schemes of the coordinated expected profit between the SC members are discussed. Through a reasonable design of the option contract, a Pareto improvement can be achieved with the SC being coordinated. All of our findings are illustrated using numerical examples.